Funkcionalna magnetna stimulacija - nova obetavna metoda zdravljenja žensk z urinsko inkontinenco - But, Igor (Zdravniški vestnik, 2009)
Background. For urinary incontinence there are different treatment options available and among them we are in favor of those, which are the least aggressive and are similarly efficient at the same time. In the last decade there has been an increasing body of evidence suggesting that the functional magnetic stimulation (FMS) might be a new and promising treatment modality for treating of women with urinary incontinence. FMS has been applied to pelvic floor therapy and the treatment of urinary incontinence for the first time in 1999. Contrary to electrical stimulation, FMS aims to stimulate the pelvic floor muscles without insertion of a vaginal probe. During the treatment patient is positioned in a special chair. Under the seat is a magnetic field generator which is producing a pulsating magnetic field which is penetrating the perineum. Structures such as pudendal nerves can therefore be magnetically stimulated without patient's discomfort or inconvenience of probe insertion as it may be true for electrical stimulation.One of the drawbacks of FMS with magnetic chair is the need for repeated office-based treatment, what may represent a major burden for patients and also for national healthcare system. Therefore we developed a new small magnetic stimulator producing electromagnetic pulses which penetrate either the perineum or pubic bone and thus stimulate the pelvic floor and detrusor muscle. One of advantages of this small portable stimulator apart of its clinical eficacy is a continuous 24-hours stimulation, which can be performed either at home/work or during different activities. Conclusions. In this article we are presenting the literature overview regarding magnetic stimulation including our initial experiences with this new treatment method. Based on our clinical results we feel that FMS represents a new and noninvasive treatment method for urinary incontinence.
Keywords: Electric Stimulation Therapy; Električna stimulacija, zdravljenje; magnetna stimulacija; therapy; Urinary Incontinence; Urinska inkontinenca; Zdravljenje